FREKUENSI DAN KONTRIBUSI ENERGI DARI SARAPAN MENINGKATKAN STATUS GIZI REMAJA PUTRI - Zana Fitriana Octavia (JURNAL RISET GIZI, 2020)
Background : Females adolescence are at high risk of chronic energy deficiency and iron-deficiency anemia, therefoe they require adequate energy for optimal growth and development. The common nutritional problem in adolescence are skipping breakfast and inadequate breakfast energy. The level of breakfast consumption for adolenscence in Indonesia was relatively low. Breakfast is useful to provide energy storage for activities in school. Irregular breakfast habits and inadequate breakfast energy could decrease productivity and nutritional status of adolescent.Objective: To determine the correlation between frequency of breakfast and contribution of breakfast energy with the nutritional status of females adolescence.Method: This study was a cross sectional design. The subjects were students on 8th and 9th grade in Madrasah Tsanawiyah aged 13-15 years. Frequency and contribution of breakfast energy were obtained from interviews with questionnaires. The nutritional status of females adolescent were obtained by using BMI z-scores according to age. The data were processed and analyzed using Gamma Sommers’ correlation test.Results: There was correlation between frequency of breakfast with the nutritional status of females adolescence (p = 0.033). There was correlation between contribution of breakfast energy with the nutritional status of females adolescence (p = 0.039).Conclusion: Frequency of breakfast was correlated with nutritional status of adolescence girls. The contribution of breakfast energy was also correlated with the nutritional status of females adolescence.